Unveiling the Effect of Age and IgE Level on Alopecia Areata: Insights from Comparative RNAseq Analysis - Liu H; Yang S; Xian H; Liu Y; Zhang Y; Chen Y; Xu Y; Liu J; Yang B; Luo Y (Clinical, Cosmetic and Investigational Dermatology)
Huiting Liu,* Sai Yang,* Hua Xian, Yinghui Liu, Yan Zhang, Yangxia Chen, Yingping Xu, Jun Liu, Bin Yang, Ying Luo Department of Dermatology, Dermatology Hospital, Southern Medical University, Guangzhou, 510091, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin Yang; Ying Luo, Department of Dermatology, Dermatology Hospital, Southern Medical University, No. 2 Lujing Road, Yuexiu District, Guangzhou, People’s Republic of China, Email yangbin1@smu.edu.cn; luoyingmab@yahoo.comBackground: Alopecia areata (AA) is a common autoimmune disease, causes sudden hair loss on the scalp, face, and sometimes other areas of the body. Previous studies have suggested more severe manifestations and higher recurrence rates in children than in adults. Moreover, pediatric AA patients with atopic predisposition often exhibit elevated IgE levels, early onset, and a poor prognosis.Purpose: This study aimed to investigate the impact of age and IgE levels on AA by conducting RNA sequencing on scalp samples from AA patients with atopic predisposition, age-matched healthy controls, and AA samples with varying IgE levels.Patients and Methods: We employed the single-sample Gene Set Enrichment Analysis (ssGSEA) algorithm in conjunction with gene expression analysis to assess immune infiltration. Differential gene expression analysis was performed using the DESeq package in R. Immunohistochemical staining and qPCR was performed to validate these findings.Results: Our results revealed a more pronounced inflammatory immune infiltration in AA patients across all age groups compared to healthy controls. Pediatric AA was characterized by an upregulation of genes controlling inflammatory responses, such as the IFN-γ pathway and JAK-STAT cascade, contrasting to adult AA. Compared to age-matched healthy controls, pediatric AA patients exhibited a significant increase in the infiltration of B cell subtypes, mast cells, and regulatory T cells. Additionally, high IgE levels in AA patients led to the upregulation of IFN-γ pathway genes, compared to AA patients with normal IgE levels.Conclusion: In summary, the heightened immune and inflammatory responses, along with the more significant infiltration of immune cells in pediatric AA with atopic predisposition, may explain the increased clinical severity and recurrence rates. Dissecting these molecular mechanisms sheds some light on the contributions of age and IgE to the pathogenesis and progression of AA, revealing potential age-specific and allergy-related therapeutic targets.Keywords: alopecia areata, age, IgE, immune response, inflammatory response